DEVELOPMENT TRENDS INNOVATIONS IN THE WORLD - N.A., Prodanova (Farabi Journal of Social Sciences, 2019)
Abstract. The article analyzes the theoretical and practical issues of researching the financial market and the impact of innovation on the empowerment of financial and non-financial institutions. Innovative development of society has taken on particular importance in recent years in the era of virtualization, internetization and cloud technologies, when new financial instruments appeared. These technologies provide the ability to transfer money to other countries and continents, make instant payment for goods and services, save and generate information in the database, conduct operations with virtual currencies, receive and provide loans between individuals and legal entities. The study, some of the findings of which are presented in this article, is devoted to current trends in the development of the financial market in the context of diversification of innovations, including on the stock and currency exchanges. Object of study ‒ the global financial market. The subject of the research is innovative processes in financial markets. The purpose of the study is to identify trends and prospects for the development of innovative processes in financial markets. The research methodology is based on the logical alignment of the material and on the analysis of the state of the global financial market and drawing conclusions based on the results. The scientific and practical significance of the work consists in the new presentation and systematization of innovative processes in financial markets. Results of the research: further development of the financial market requires the development of information technology, the banking sector and the stock market.